2017
DOI: 10.1002/jcp.25500
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton Aberrations in Alkaptonuric Chondrocytes

Abstract: Alkaptonuria (AKU) is an ultra-rare autosomal genetic disorder caused by a defect in the activity of the enzyme homogentisate 1,2-dioxygenase (HGD) that leads to the accumulation of homogentisic acid (HGA) and its oxidized product, benzoquinone acetic acid (BQA), in the connective tissues causing a pigmentation called "ochronosis." The consequent progressive formation of ochronotic aggregates generate a severe condition of oxidative stress and inflammation in all the affected areas. Experimental evidences have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…In the present study, we report variations in primary cilia prevalence and length for AKU chondrocytes which may be associated with alterations in the organization of actin (Fig. ) and other cytoskeletal components (Geminiani et al, ). The filamentous microtubule structure is transformed in AKU chondrocytes, forming aggregates at the cell periphery (Geminiani et al, ).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In the present study, we report variations in primary cilia prevalence and length for AKU chondrocytes which may be associated with alterations in the organization of actin (Fig. ) and other cytoskeletal components (Geminiani et al, ). The filamentous microtubule structure is transformed in AKU chondrocytes, forming aggregates at the cell periphery (Geminiani et al, ).…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, Geminiani et al (2016) recently reported that both actin and microtubule cytoskeletal elements are disordered in AKU chondrocytes. In addition to alterations in cell shape, actin stress fibre formation is increased in AKU chondrocytes accompanied by the formation of actin bundles in the nuclear periphery (Geminiani et al, 2016). The disruption of actin organization and dynamics may have consequences for the maintenance of chondrocyte phenotype (Brown & Benya, 1988), mechanotransduction (Ohashi, Hagiwara, Bader, & Knight, 2006;Wright et al, 1997), and may also influence chondrocyte function through the primary cilium.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…There are numerous findings indicating that, among the processes that lead to cartilage degradation in AKU, important roles are played by oxidative stress (Braconi et al, , , ), inflammation (Millucci et al, ), and accumulation of serum amyloid A (SAA), describing AKU as a secondary amyloidosis (Millucci et al, ,, ). More recently, the structural analysis of AKU chondrocyte cytoskeleton revealed that the organization of the three main cytoskeletal proteins (tubulin, actin, and vimentin) is altered in AKU cells (Geminiani et al, ) and that chondrocytes cultured in HGA‐added medium started developing the same alterations observed in AKU chondrocytes. Alterations in cytoskeletal tension have previously been shown to regulate the structure and function of primary cilia (McMurray, Wann, Thompson, Connelly, & Knight, ; Pitaval, Tseng, Bornens, & Thery, ).…”
Section: Introductionmentioning
confidence: 96%